2022
DOI: 10.1038/s41398-022-02157-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathological fear, anxiety and negative affect exhibit distinct neurostructural signatures: evidence from psychiatric neuroimaging meta-analysis

Abstract: Internalizing disorders encompass anxiety, fear and depressive disorders, which exhibit overlap at both conceptual and symptom levels. Given that a neurobiological evaluation is lacking, we conducted a Seed-based D-Mapping comparative meta-analysis including coordinates as well as original statistical maps to determine common and disorder-specific gray matter volume alterations in generalized anxiety disorder (GAD), fear-related anxiety disorders (FAD, i.e., social anxiety disorder, specific phobias, panic dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 179 publications
(142 reference statements)
7
33
0
Order By: Relevance
“…Additionally, our results showed smaller OFC and insula volumes in individuals with phobias compared with non-fearful controls, which is consistent with previous studies [ 19 ]. An increased GMV of the OFC has been associated with a high capacity for emotional self-regulation [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Additionally, our results showed smaller OFC and insula volumes in individuals with phobias compared with non-fearful controls, which is consistent with previous studies [ 19 ]. An increased GMV of the OFC has been associated with a high capacity for emotional self-regulation [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Morphometric analysis revealed that a cluster of superior/medial frontal areas and ACC were diminished in phobic participants. In the same vein, decreased volumes in the lateral/medial PFC cortex have been found in GAD and panic disorder [ 19 , 26 ]. However, an increased volume in the left PFC, OFC, and ACC has been found when individuals with phobia were compared with non-fearful controls [ 30 ].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations